Sustaining Layered Tolerance in Islam Nusantara: Sunan Kudus’s Legacy in Nahdliyin–Christian Relations in Kayuapu, Kudus - Moh Rosyid; Lina Kushidayati (Lakpesdam PCNU Kota Salatiga, 2025)
Islam–Christian relations at the village level are often shaped by a long history of coexistence, yet they remain vulnerable to identity anxiety, conversion concerns, and symbolic competition. In the context of Kudus, the legacy of Sunan Kudus commonly narrated as accommodative da‘wah and an ethic of respect toward other groups can function as cultural capital that stabilizes interfaith encounters. This article aims to explain how the historical context of colonialism, the development of zending/missionary activities and Islamic preaching, and the collective memory of Walisongo Islamization (particularly Sunan Kudus) have shaped patterns of Islam–Christian relations in Dukuh Kayuapu, as well as how Nahdliyin residents practice “layered tolerance” through NU/Aswaja cultural strategies (tahlil, berjanjen/shalawat, pengajian, and TPQ) within this contact zone. The study adopts a qualitative approach with a case study design in Dukuh Kayuapu, Gondangmanis Village, Bae Subdistrict, Kudus; data were collected through limited participant observation, semi-structured interviews with purposively selected informants (NU figures, cross-generational residents, church council/pastor, and village officials), and document analysis, and were analyzed thematically. The findings show that tolerance in Kayuapu operates as a governance of difference: social harmony is maintained through everyday contact (neighborly interaction, bereavement solidarity, and collective work), while theological boundaries are selectively managed through relatively subtle boundary maintenance. Aswaja traditions function as a “protective infrastructure” that strengthens internal cohesion and reduces conversion anxiety without provoking open conflict, while the legacy of Sunan Kudus serves as cultural legitimation for an ethic of interfaith respect. The study recommends strengthening cross-community humanitarian social-contact spaces, formulating mutually agreed codes of encounter for sensitive issues, reinforcing moderate religious literacy within each community, and activating the narrative of Sunan Kudus’s legacy as a public moral language to prevent the escalation of friction in interfaith contact zones.